ANALISIS PRAKTIK PENGHINDARAN PAJAK INTERNASIONAL OLEH PERUSAHAAN MULTINASIONAL DAN EFEKTIVITAS REGULASI ANTI-AVOIDANCE: KAJIAN PUSTAKA - Loso Judijanto (Jurnal Salome : Multidisipliner Keilmuan, 2025)
International tax avoidance practices by multinational companies pose a serious challenge to the global taxation system, especially amid complex regulations and differences in tax rates between countries. This study aims to analyse various common tax avoidance strategies, such as profit shifting, aggressive transfer pricing, and the use of tax havens, and to evaluate the effectiveness of anti-avoidance regulations that have been implemented in various jurisdictions. Through a literature review, it was found that the implementation of rules such as General Anti-Avoidance Rules (GAAR), Controlled Foreign Corporation (CFC) rules, and arm's length-based transfer pricing regulations can reduce the scope for companies to shift profits. However, the effectiveness of regulations is greatly influenced by cross-border policy harmonisation, law enforcement capacity, and the adaptation of increasingly complex avoidance strategies. This study emphasises the importance of international collaboration, institutional strengthening, and the use of technology to enhance transparency and fairness in the global tax system.